(Re)Mediating Holocaust Survivor Testimony - Schwartzman, Roy (Advances in Social Sciences Research Journal, 2020)
As the number of Holocaust survivors declines, their live eyewitness testimony will be preserved and communicated via other media. This transformation prompts a key question. What value can personal testimony have when disembodied and presented in a medium more manipulable by the audience? The response addresses three types of mediated testimony: the first televised broadcast of a Holocaust survivor’s story, on the 1953 U.S. television series This Is Your Life; archival video testimonies; and “unsettled testimony” consisting of less structured, first-person testimonies gathered by the author that reveal the challenges of discursive representation. Each type of testimony offers distinct advantages and limitations in reducing prejudice and fostering understanding.